Corporate Foresight, Organizational Learning, And Performance Of Smes In Uae: Moderating Role Of Digital Transformation And Mediating Role Of Innovativeness - Ahmed Almujaini, Hasan Saleh Mohamed (2021)
The title of corporate foresight is assumed as a capability that includes any structural or cultural element that enables the company to detect discontinuous change early. The purpose of present study is to examine the direct impact of corporate foresight, and organizational learning on the performance dynamic of SMEs as working in United Arab Emirates (UAE). In addition, this study tries to analyze the moderating as well as mediating effect of digital transformation and innovativeness on the relationship between exogenous and endogenous constructs. A sample of 576 questionnaires were distributed among the owners/managers of different SMEs as working in the region of UAE. The data was analzyed through descriptive and two step approaches where structural equation modelling (SEM) under Smart PLS was found to be very much help to examine the direct and indirect relationship between the study variables. The study findings show that there is a insignificant but positive impact of corporate foresight on organizational performance whereas significant impact of organizational learning on organizational performance. Furthermore, the study found an evidence for the moderating effect of digital transformation between organizational learning and innovation. Additionally, it is observed that innovativeness mediates the relationship corporate foresight and performance dynamics. The study findings suggest that for exploring the relationship between corporate foresight, digital transformation and organizational the role of innovation and digital transformation is quite significant.